Networks and Fault Lines: Understanding the role of housing associations in neighbourhood regeneration: a network governance perspective - van Bortel, Gerard (A+BE | Architecture and the Built Environment, 2016)
The changing role of housing associations in neighbourhood regeneration This study aims to increase our understanding of the role of social housing organisations in neighbourhood regeneration governance networks, in order to enhance the performance and outcomes of these networks. Our understanding of how governance networks work is still limited, especially concerning the role of non-state actors like housing associations. Hierarchical government steering is increasingly mixed with market mechanisms and networked forms of decision-making. These shifts in governance often result in more complex decision-making that can easily lead to deadlocks, low-quality outcomes and ambiguous anchorage of democratic principles. Neighbourhood regeneration takes place in rather exceptional governance networks. The organisations involved, and the problems at hand, are place-based. Actors, like housing associations, local authorities and community organisations, are more or less ‘locked’ into the regeneration network and need to collaborate in order to solve the problems. The complexity of neighbourhood renewal processes is often very high, due to the large number of actors involved, and the combination of insufficient housing quality, lack of affordability and supply, along with social and economic problems that need to be addressed. Housing associations focus on the delivery of affordable decent quality housing; but, in many countries—like the Netherlands and England—these organisations also have an important role in neighbourhood regeneration. Housing associations are non-profit organisations that provide housing for low and moderate-income households. They operate largely autonomously from the government, although they are often strongly regulated and dependent on government subsidies. Housing associations in England and the Netherlands share many organisational characteristics and hybrid third-sector values emerging from the need to balance social and economic objectives. They have largely similar tasks and responsibilities, but work in very divergent contexts. This study devotes careful attention to the contingencies of time and place of decisionmaking in order to regenerate insights that are also relevant outside the case-study areas. Therefore, this study places Dutch and English housing associations in their respective political economies, welfare regimes and rental housing systems. The study also highlights the ambiguous position—between state, market, and society—of housing associations. Neighbourhood regeneration evolved from slum clearance and complete area redevelopment in the 1950s and 1960s, towards more integral place-based approaches—in the 1970s and 1980s—with a stronger emphasis on improving the existing housing stock and involving local communities. The nature of the involvement of housing associations in neighbourhood regeneration has changed over time in response to government policies, public opinion, their own strategies, and the strategies of their umbrella organisations. In both England and the Netherlands, their increasingly prominent role —especially after the start of the new millennium—was driven by pressures on housing associations to take a leading role in neighbourhood regeneration. A governance network perspective on neighbourhood regeneration The emergence of the ‘network society’ has led to a fragmentation of power and resources. This fragmentation has led to increased interdependence of actors; public, private and community actors need to collaborate to solve problems. This study uses a governance network approach to explore the complexity and uncertainties involved in neighbourhood regeneration decision-making. The study explores five interrelated questions [see Chapter 1, §1.2], each related to a component of a theoretical framework on decision-making in a network setting. These questions involve context, networks, actors, processes and outcomes. In order to answer the research questions, a qualitative, comparative, longitudinal exploration based on a case study methodology, was conducted. To ensure that comparable cases were explored, similar ‘focal actors’ were chosen (i.e. housing associations), as well as similar ‘policy outputs’ as starting points for the study (i.e. the drafting of neighbourhood regeneration plans). Based on these criteria, housing association Midland Heart, and the neighbourhood Lozells in North/West Birmingham, was selected as the English case study. In the Netherlands, housing association De Huismeesters, and De Hoogte, a neighbourhood in Groningen, were selected. Personal accounts have been an important data source for this study; 70 interviews with 45 different individuals were conducted between 2007 and 2014 in Groningen, and Birmingham. In addition, for the case study in The Hague (Chapter 5), around 25 interviews were conducted in 2004. That chapter was a first introduction to the explanatory capabilities of the network governance perspective. Research results The introductory chapter explores contextual factors—such as economic, social and political developments—that affect the role of housing associations in neighbourhood regeneration. Chapters 3 through 7 contain sections which describe the context relevant to that specific chapter. Chapter 8 is more reflective in nature and discusses the impact of post-crisis ‘Big Society’ (UK), and Participation Society (NL) government policies, as contingency factors for the role of housing associations in relation to local communities. Finally, Chapter 9 brings all the components of the theoretical framework together and especially reflects on the significant impact of contextual developments on the role played by housing associations in neighbourhood regeneration decision-making, and delivery. This research also highlighted the strong network relationships between housing associations and local authorities, but also revealed the often troublesome interactions between housing associations and residents. The title of this thesis: “Networks and Fault lines” is intended to reflect this. This research took place in a period of unexpectedly dynamic economic, social and political developments, i.e. the global financial crisis, the housing-market downturn, government austerity, and a more restricted interpretation of the state’s role in delivering welfare services. The impacts of these developments varied across the two cases. The Dutch housing association proved more resilient to contextual developments than its English counterpart; especially its ability to continue the neighbourhood investment programme. National government funding was less important to the Dutch housing association: the organisation already had access to neighbourhood regeneration investment resources. Other contextual factors, such as the characteristics of the national political economies, welfare and housing systems, indirectly affected the role played by housing associations. These factors mainly influenced the characteristics of the governance networks and the decision-making processes within these networks. Explored through the networks component are the characteristics of the governance networks that housing associations participate in: interdependencies, strength of network relations, and the nature of the coordination mechanisms that underline decision-making. The key concepts to exploring networks are introduced in Chapter 2, and further developed in Chapters 3, 5 and 7. We found high levels of uncertainty, generated by the variety of, and the interdependencies between, actors, the closed-mindedness of actors to the arguments of other parties, and the changes in composition of the governance network. For example, the research found substantial cross-national differences, and indications that network characteristics change and fluctuate over time. In contrast to the situation in Groningen, the dependency of the Birmingham network on external government funding negatively affected the stability and the performance of that network. In Groningen, top-down government intervention also negatively affected the stability of the network, but for other reasons. The, short-lived, abundance of resources for regeneration led to such a high number of new actors, issues, goals and decision-making arenas that the governance network was unable to function properly for some time. The network actors increased the complexity of policy games of their own volition. Sometimes, this was induced by the national government, when local network actors responded to steering instruments such as government subsidies. This led to more network complexity and dynamics in the form of new goals, network actors and decision-making arenas. The third research component—the actors— explored the perceptions and objectives of housing associations, and other key network actors concerning neighbourhood regeneration investments and activities. Housing associations in both case-study areas took a prominent role in neighbourhood regeneration activities, and collaborated closely with local authority departments in drafting regeneration plans. The housing associations regarded improving the quality and variety of the local housing stock as an important element in creating a more mixed community, and retaining and attracting more affluent households. The local authorities supported this predominantly longterm ambition. Residents were more concerned with tackling short-term liveability issues, such as anti-social behaviour, crime and litter. The role of housing associations changed during the 2007-2014 fieldwork period. From occupying a leading role in the regeneration process—in partnership with the local authority—at the start of the exploration in 2007, this role transformed into a more facilitating and supporting role. This appears to have been brought about by two related factors: a serious decline in available regeneration resources, and an increased emphasis on the responsibilities of individual residents and local communities under the influence of the Participation Society agenda, in the Netherlands, and the Localism agenda in England. Residents and private-sector organisations were rarely directly involved in regeneration decision-making. With a little hindsight, one could formulate the contention that these actors were not fully represented in the governance network because the incumbent network actors (i.e. the housing associations and local authorities) chose the devil they knew. They opted for state involvement to acquire investment resources, rather than facing the uncertainties that would have resulted from expanding the network to include residents and private-sector organisations as full and mature network actors. Decision-making processes constitute the fourth component of this study. It explored the decision-making interactions inside the neighbourhood regeneration networks, with a special focus on the interaction strategies used by housing associations. This study found that housing associations in the Groningen and Birmingham cases had a prominent and often leading role in the policy arenas where regeneration policies were developed. National governments in both countries had a strong impact on how these processes evolved, leveraged by the alluring investment resources offered by national regeneration programmes, and the preconditions accompanying these resources. Decision-making took place in arenas that almost exclusively consisted of housing association and local authority professionals. Residents were largely given a consumerist role in the process: their views on neighbourhood needs were collected through various instruments to involve residents, such as surveys and street interviews. Their views were, implicitly, taken into account in the decision-making. Residents were most often not part of these processes and not involved in the development of regeneration investments plans. Not all decision-making arenas were closed to residents. The housing associations in both case-study areas did involve residents as co-decision-makers in more ‘hands-on’ neighbourhood issues such as improving playareas, tackling garbage and litter problems. Decision-making conflicts and deadlocks were rather limited in the investigated governance networks. There was a strong impetus for the housing associations and the local authorities to reach agreements: no consensus would very likely mean no national government funding. Housing associations and local authorities used rather traditional instruments to facilitate decision-making, such as limiting the number of actors involved, and enforcing strict time constraints on decision-making processes. Outcomes are the fifth and last component of this study. In this component we explored how the network—and housing associations in particular—contributed to decision-making and neighbourhood regeneration outcomes. It is evident that the housing associations in the case-study areas contributed significantly to neighbourhood regeneration activities, not only because they channelled considerable investments into the areas, but also due to their strong network relations and frequent interactions with government agencies and local communities. The actions of network actors have improved the quality of some parts of the housing stock. Joint projects have been delivered to improve the public realm and contribute to neighbourhood safety. The research found that actors used very divergent process, input, output and outcome yardsticks to measure success, ranging from the number of projects and activities started, to the amount of money spent, the increase in resident satisfaction, the number of decision-making conflicts overcome, and the improvement achieved in quality-of-life indicators. These yardsticks changed over time and varied from actor to actor. This demonstrated how fluid the assessment of regeneration outcomes can be. New rounds of decision-making, as well as new network actors, led to a review of old decisions, sometimes with a different assessment of the outcomes achieved. Challenges for governance network approaches The governance network perspective has supported the exploration of the role played by housing associations in neighbourhood regeneration decision-making. It has increased our understanding of the complexity and the uncertainties involved in networked forms of decision-making. Governance network theory helped us identify instruments and strategies used by housing associations and local authorities to support regeneration decision-making. The governance network perspective is a rather new academic discipline that can be further developed. This study contributed to this development by addressing some issues and challenges; firstly, the role of residents in decision-making arenas, and secondly, the assessment of governance network outcomes. The theoretical and methodological implications of residents as neighbourhood regeneration co-producers Policy-makers expect a more active role of residents and local communities in the co-production of neighbourhood regeneration. This more inclusive approach may contribute to the quality and legitimacy of decisions made in governance networks, but the efficiency of decision-making will most probably not benefit. The trade-off between efficiency and legitimacy that arises from increased resident involvement is a challenge that calls for the further development of the governance network theory. This research suggests several avenues that could be followed to address this challenge. Firstly, a more extensive use of Habermas’s Theory of Communicative Action, as explored in Chapter 8, might be undertaken to supplement the governance network theory. Secondly, more use could be made of the body of knowledge and theories developed in England during the New Labour government (1997-2010), which was often explicitly concerned with networks that linked governments with citizens and local communities [see Chapter 9]. The assessment of governance network outcomes Co-production of neighbourhood regeneration can lead to more democratic and inclusive approaches to decision-making. This is likely to result in better outcomes, but not necessarily in greater consensus among the actors involved. Within network governance approaches, there is a tendency to define satisfactory outcomes as those that enjoy the greatest joint support of the actors involved in the process. More inclusive approaches, which engage a wider range of actors, might appear to be less successful as the benchmark of satisfaction is raised to include a wider range of preferences and experiences. Therefore, we need a more refined assessment of outcomes produced by increasingly heterogeneous networks. Governance network approaches could develop methods – or develop connections with other theories and methodologies – that help evaluate the success of governance networks by combining substantive regeneration outcomes, actor and stakeholder satisfaction, and network learning. Preventing ‘cherry picking’ in the use of assessment yardsticks is essential, given the disinclination of actors to closely scrutinise the outcomes produced by governance networks (as found in this research). Further development of network governance approaches may increase our understanding of how actors construct the yardsticks to evaluate success, and provide tools to facilitate a more comprehensive assessment of network outcomes [See chapter 9]. Housing associations as champions of networks in vulnerable neighbourhoods This research demonstrated that housing associations can play an important stabilising and cohesion-enhancing role in neighbourhood regeneration networks. Their interests are vested in the value of the local housing stock, and this financial incentive secures some level of commitment to vulnerable neighbourhoods. Their hybrid characteristics enable housing associations to collaborate with community, market and government organisations. Moreover, their professional capabilities and their relatively-easy access to resources allow them to champion neighbourhood needs, in cases where communities lack the capacity or cohesiveness to champion their own. Using the leeway that housing associations have, as a hybrid organisation, is an extremely delicate exercise. They should seek a balance between the very different and variable expectations of the outside world. This balancing act is only attainable when housing associations can combine proficiency in network management, with increased accountability. Each neighbourhood is different, and housing associations should take a role that is appropriate to each neighbourhood. To do this, they should increase their knowledge of the neighbourhood challenges and assess the capabilities of residents and the local community to address these problems. Housing associations can support the development of governance networks to address these problems by helping craft networks in such a way that they include all relevant parties, and by providing small but stable funding to support network development and by improving accountability in decision-making processes. There are strong arguments for housing associations to take a central role in neighbourhood regeneration. Housing associations are among the most prominent frontline agencies supporting vulnerable people and places. Through their housing stock, they are literally ‘anchored’ in the most deprived communities. Housing associations should not become the ‘jack-of-all-trades’ in neighbourhood regeneration, but can help develop, nurture and maintain well-functioning and stable regeneration networks which vulnerable neighbourhoods need. Housing associations can be the long-haul champion that neighbourhoods and local communities need.